A comparison of software-based staff notation and indigenous memorization methods in teaching the nyunga nyunga mbira - Muranda, R (Midlands State University, 2023)
The article is based on an experimental research to compare a software-based staff notation and the traditional African methods in the teaching of the nyunga nyunga mbira to grade six classes in the Arts and Culture learning area at Pretoria Chinese School in South Africa. 30 pupils were exposed to the nyunga nyunga mbira a Zimbabwean indigenous musical instrument. The group had 15 learners each with one acting as the control group and the other as the experimental one. Some of the children belonged to the following: Afrikaner, British, Chinese Indian, Italian, Korean, Ghanaian, Sotho, Shona and Zulu Cultures. The research was conducted from September 2010 to November 2010. The Kukayiwa tune with four variations was taught to both groups. Whereas the control group was taught to play the instrument through the rote method, the experimental received instruction using the computer-assisted approach. Proceedings in each of the teaching sessions were diarized. Audio-video recordings and photographs of pupils’ activities were made. Assessments of the pupils’ performance in both groups was done to check on the effectiveness of each of the methods under research. The results showed that both methods were effective in teaching the instrument. Pupils in the control group began with a better performance than their counterparts. However, the experimental group became more consistent than the control group towards the end of the research. The pupils involved in this research were able to play the nyunga nyunga mbira together as an ensemble. The instrument proved that it could fit well in the core components (art, dance, drama and music) of the Arts and Culture. The nyunga nyunga mbira music performed during the research was effective in storytelling, dance, movement and drama, especially with the extra afternoon session learners. Further research should be conducted to verify the software based method and all that it offers to the learners in the teaching of the nyunga nyunga mbira.